Otoritas Komisi Penyiaran Indonesia dalam Pengaturan Isi Siaran - Dian Sukmawati; Ade Armando (Jurnal Komunikasi Global, 2019)
Although the Indonesian Broadcasting Commission (KPI) supervised all of the television programs, there are a lot of programs getting a warning because of breaking the rule of P Broadcasting Code of Conduct (P3) and Broadcasting Program Standard (SPS). Focusing on program Pagi-Pagi Pasti Happy, this research investigated the authority of KPI in terms of being a watchdog of television content in Indonesia. This research deployed political economy theory because it has studied not only media analysis in general but also the problems faced by the media industry and who controlled media. To criticize the authority of KPI in maintaining a code of conduct over the broadcasting content, three KPI’s commissioners, two television program representatives, and a media observer were interviewed. Based on interviews, the researcher found that dialogue preferred by KPI in supervising the television content confirmed that the current KPI’s commissioner has compromised with private television stations. KPI is more likely to support the existing television business system nowadays to gain maximum profit for the media investor. The findings suggest that role as KPI’s commissioner has been used to gain more power in the future.